Electrocardiogram Acquisition Errors or Myocardial Infarct - Sari U. M. Vanninen; Kjell C. Nikus (Case Reports in Cardiology, 2011)
Incorrect lead placement may result in unnecessary therapeutic interventions. We present a case report of 53-year-old man with new inferior T-wave inversions in the 12-lead electrocardiogram (ECG) noted during routine followup of hypertension without any cardiovascular symptoms.